1998
DOI: 10.1111/j.1545-5300.1998.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Schizophrenic Patients' Families and Normal Families in China, Using Chinese Versions of FACES‐II and the Family Environment Scales

Abstract: The lack of measures that systematically evaluate the characteristics and functioning of Chinese families is hindering the development of appropriate family interventions for schizophrenia in China. We assessed the reliability and validity of revised and adapted Chinese versions (CV) of the Family Adaptability and Cohesion Evaluation Scales (FACES-II-CV) and the Family Environment Scales (FES-CV) and administered these instruments to 120 respondents from families with a schizophrenic member and 126 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 15 publications
11
61
0
2
Order By: Relevance
“…This is consistent with the notion that Whites (non-Hispanics) perceived their family environments to be ones in which family members were more assertive, self-sufficient, and able to make autonomous decisions (Axelson, 1993). This independence, especially in children, was commonplace and accepted (Phillips et al, 1998), whereas children's independence, particularly in African Caribbean families, was undesirable, discouraged, and seen as undermining parental authority (Giles, 1990). African Caribbean women's responses to the open-ended questions supported the results of the FES, which showed that these women experienced alack of independence and autonomy.…”
Section: Qualitative F I N D I N G Ssupporting
confidence: 60%
“…This is consistent with the notion that Whites (non-Hispanics) perceived their family environments to be ones in which family members were more assertive, self-sufficient, and able to make autonomous decisions (Axelson, 1993). This independence, especially in children, was commonplace and accepted (Phillips et al, 1998), whereas children's independence, particularly in African Caribbean families, was undesirable, discouraged, and seen as undermining parental authority (Giles, 1990). African Caribbean women's responses to the open-ended questions supported the results of the FES, which showed that these women experienced alack of independence and autonomy.…”
Section: Qualitative F I N D I N G Ssupporting
confidence: 60%
“…In view of the non-existence of research findings on the assessment of parental control based on indigenous Chinese concepts, the present findings can be regarded as ground-breaking. Because there are few instruments assessing Chinese psychosocial functioning (Shek, 2002) and the lack of objective family assessment tools has adversely affected the development of family intervention work in the Chinese context (Phillips et al, 1998), the present study can be regarded as a constructive response.…”
Section: Discussionmentioning
confidence: 99%
“…Family-level social support was assessed through three subscales: family cohesion (16 questions, Cronbach's alpha = 0.73), family adaptability (14 questions, Cronbach's alpha = 0.77), and sibling support (16 questions, Cronbach's alpha = 0.80). Subscales were created by using questions from the Chinese versions of validated surveys, the Family Adaptability And Cohesion Evaluation Scales II (FACES-II-CV), and the Family Environment Scales (FES-CV) (Olson, Portner, and Bell, 1982;Phillips, West, Shen, and Zheng, 1998;Phillips, Zheng, and Zou, 1999). Responses for questions on family cohesion (e.g., family members are supportive of each other during difficult times, family members know each others' close friends) and family adaptability (e.g., discipline is fair in our family, our family tries new ways of dealing with problems) were provided on a 5-point Likert-type scale ranging from "almost never" to "almost always."…”
Section: Peer Smokingmentioning
confidence: 99%